Efektivitas Pengelolaan Aset Tetap pada Dinas Tenaga Kerja dan Transmigrasi Kabupaten Belu - Ricardo De Jesus Martins; Petrus E. de Rozari; Aldarine Molidya (Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2025)
This research aims to determine the effectiveness of fixed asset management at the Manpower and Transmigration Service, Belu Regency, East Nusa Tenaggara Province. The type of research used in this research is field research. The research approach used in this research is a qualitative approach. The type of data used in this research is qualitative and quantitative data, while the data sources are primary and secondary data, as well as data collection techniques through observation, interviews and documentation. There were 8 informants in this research, including the Head of Department, Treasurer of Goods and Head of Division as well as 5 personnel staff at the Manpower and Transmigration Service of Belu Regency. The results of the research show that the effectiveness of fixed asset management at the Belu Regency Manpower and Transmigration Service has indicators that are effective and those that are not yet effective. The implementation that has been effective is based on the indicators of program objectives and accuracy of program targets. Implementation that has not been effective is in the indicators of program socialization and program monitoring. Program socialization is seen as ineffective because the sub-focus of the intensity of socialization cannot be understood and management is not running well.